Screening of Surface-Exposed Lipoproteins of Leptospira Involved in Modulation of Host Innate Immune Response - Kumar, Ajay; Varma, Vivek P.; Faisal, Syed M. (Frontiers in Microbiology, 2022)
Leptospira, a zoonotic pathogen is capable of causing both chronic and acute infection in susceptible host. Surface exposed lipoproteins play major role in modulating the host immune response by activating the innate cells like macrophages and DCs or evading complement attack and killing by phagocytes like neutrophils to favour pathogenesis and establish infection. In this study we screened some of surface exposed lipoproteins which are known to be involved in pathogenesis for their possible role in immune modulation (innate immune activation or evasion). Surface proteins of Len family (LenB, LenD, LenE), Lsa30, Loa22 and Lipl21 were purified in recombinant form and then tested for their ability to activate macrophages of different host (mouse, human and bovine). These proteins were tested for binding with complement regulators (FH, C4BP), host protease (plasminogen, PLG) and as nucleases to access their possible role in innate immune evasion. Our results show that of various proteins tested Loa22 induced strong innate activation and Lsa30 was least stimulatory as evident from production of pro-inflammatory cytokines (IL-6, TNF-a) and expression of surface markers (CD80, CD86, MHCII). All the tested proteins were able to bind to FH, C4BP and PLG, however Loa22 showed strong binding to PLG correlating to plasmin activity. All the proteins except Loa22 showed nuclease activity albeit with requirement of different metal ions. The nuclease activity of these proteins correlated to in vitro degradation of Neutrophil extracellular trap (NET). These results indicate that these surface proteins are involved in innate immune modulation and may play critical role in assisting the bacteria to invade and colonize the host tissue for persistent infection.